PERSEPSI MAHASISWA JURUSAN AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS TANJUNGPURA TERHADAP AKUNTANSI SYARIAH - B41111048, Amanah Hijriah (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
In the last decade sharia institution has grown so rapidly, both profit and nonprofit instituted. Since 2003, for the first time IAI set SFAS 59, Accounting for Islamic Banking. Until now, IAI has set SFAS 101-111 for each institution needs sharia, such as BUS, UUS, SRB, BMT and others. Accounting sharia in West Kalimantan is still a new thing. Needs of professionals and experts in this field is needed. This study aims to determine how students' perceptions of sharia accounting. The variables in this study are divided into internal factors indicator consists of attention, needs, knowledge and interests. And external factors such as environmental indicators and opportunities. The results showed a mean attention for (PR) 4.08, requirement (KB) 3.70, knowledge (PG) 3.24, interest (MN) of 3.41 and the environment (LK) 3.89. Indicators of knowledge with the lowest position, ie 3.24 indicates that knowledge of sharia accounting students still need to be improved, either through formal education and informal campus off campus. But overall the students have a positive perception of sharia accounting. Keywords: perception, student, shariaaccounting